Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Defining optimal elevation thresholds for mangrove restoration through dynamic tidal simulation: Evidence from morphological and physiological assessment of five species in Zhanjiang Bay, China - Jianjian Huang; Bing Yang; Xin Zhou; Jie Chen; Suqing Liu; Kangyi Deng; Xiuxuan Lin; Yiting Chen; Ruixuan Wang; Yuzhong Zheng; Qinghan Wu; Hui Zhu; et al. (Ecological Engineering, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Mechanistic bifurcation and coordination modification in peroxymonosulfate activation by cobalt catalysts - Yan Zhao; Fan Wu; Xiaojiao Chen; Yingyi Wang; Li Hui; Hong Lin (Journal of Environmental Chemical Engineering, 2026)

Elemental sulfur-enhanced hydrothermal stabilization of arsenic in arsenic sulfide sludges: Mechanism of sulfur-induced structure transformation and practical application - Hui Xu; Wanlan Wu; Qiujing Xu; Yong Ke; Yun Li; Cong Peng; Lin Yu; Zhumei Sun; Yunyan Wang; Xiaobo Min (Journal of Environmental Chemical Engineering, 2026)

A hybrid soft sensing framework for cost-effective monitoring of nitrogen in wastewater treatment under data scarcity - Yaorong Shu; Zhilin Li; Jinpeng Chen; Xiaoyu Lin; Wenjun Liu; Juan Mao; Hui Liu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu (Journal of Environmental Chemical Engineering, 2026)

Sedimentological and reservoir characteristics of Carboniferous–Permian shales in the northern Songliao Basin and surrounding areas, Northeastern China - Honggang Cheng; Deyong Li; Xuefeng Bai; Lin Jiang; Qinghua Huang; Dehai Wang; Hui Wang; Shujuan Xu; Xueqiong Wu; Wei Duan; Chengzao Jia (Journal of Asian Earth Sciences, 2026)

The accumulation and regulation mechanisms of microbial residual carbon along an elevation gradient in dryland mountains - Danbo Pang; Lin Chen; Ansa Rebi; Hui Li; Guangyao Shi; Yang Hu; Jinxing Zhou; Xilu Ni; Xuebin Li; Mengyao Wu; Geshere Abdisa Gurmesa (Fungal Ecology, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Facet-controlled Pt/CeO2 unlocks low-humidity HCHO oxidation via terminal hydroxyls - Juanjuan Gong; Ruicheng Wang; Yilong Lin; Hui Chen; Bihong Lv; Huawang Zhao; Huazhen Shen; Zhiwei Huang; Xiaomin Wu; Guohua Jing (Journal of Hazardous Materials, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Extreme precipitation during the warm growing season amplifies methane emissions and reduces non-growing season contributions in a Tibetan alpine peatland - Zhenrong Lin; Zhirang Wu; Zheng Li; Jian Hu; Hui Wang; Qingping Zhou; Shuli Niu; Jinsong Wang; Shaoying Wang; Xianhong Meng; Ruijun Long; Lei Ma (Agricultural and Forest Meteorology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Exceptional multi-organ Tilia fossils from Miocene Korea: A well-preserved fossil flower and evidence for higher diversity - Hui-Hui Chen; Qiu-Yue Zhang; Gi-Soo Nam; Lin-Bo Jia; Yao-Wu Xing (Review of Palaeobotany and Palynology, 2026)

Sedimentary evolution and its response to climate and sea level changes in the northern South China Sea over the past 60 ka - Kairui Liu; Kaikai Wu; Hui Zhang; Peng Cao; Xiaoyan Li; Lin Jia; Kunshan Wang; Lina Ai; Hongmin Wang; Shengfa Liu (Quaternary International, 2026)

New insights into the sclerite ultrastructure and affinity of early Cambrian maikhanellids from South China - Yang Hou; Hong Hua; Jin-Zhou Luo; Meng Gong; Xin-Zi Wang; Lin Bai; Zi-Hui Wu; Xue-Ting Wang; Song Zhang (Palaeoworld, 2026)

From planarization-assisted footing to halogen-induced gripping: cooperative additive engineering of molecular assembly for efficient organic solar cells - Xinrui Li; Chenghao Jiang; Xiaoyang Du; Huilin Wu; Jia Zhu; Hui Lin; Caijun Zheng; Silu Tao (Chemical Engineering Journal, 2026)

The epigenetic regulation between dietary bioactives and DNA methylation via multiple pathways - Shiye Lin; Wenqi Huang; Xincheng Wu; Juan Carlos Mejuto Fernández; Mohamed A. Farag; Hui Cao (Phytochemistry Reviews, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

Clean heating transition in China: Technological innovation, residual emission burden, and regional inequality in northern cities - Linyan Li; Yunlong Wu; Li Zhang; Huili Wang; Jieyi Li; Lin Xiang; Xiurong Hu; Jiaxuan He; Ling Jin; Xiaojun Chen; Hui Xu; Yu Lei (Sustainable Production and Consumption, 2026)

Evolution of upwelling in the southwestern Sumatra waters since the middle Holocene: Evidence from mineralogy and geochemistry - Xue Li; Lina Ai; Hui Zhang; Peng Cao; Lin Jia; Xiaoyan Li; Kunshan Wang; Kaikai Wu; Hongmin Wang; Rainer Arief Troa; Rina Zuraida; Eko Triarso; et al. (Quaternary International, 2026)

Insights into the role of pyrolysis temperature in cotransport of biochar nanoparticles and polystyrene nanoplastics in porous media - Xuanhao Lin; Ming Wu; Qusheng Li; Hui Li; Yanru Hao; Cehui Mo (Journal of Environmental Sciences, 2026)

Metamorphic evolution and geochronology of garnet amphibolite, the Dongbatu tectonic-metamorphic mélange, eastern middle Paleozoic Dunhuang Orogenic Belt, northwest China - Xue-Li Jia; Yichao Chen; Yan-Lin Zhao; Zhen M.G. Li; Hui C.G. Zhang; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Notch Signaling Regulates the Neuroprotective Effects of hUCMSCs in a Mouse Model of Cerebral Ischemia - JiaYou Zhou; Hui Su; JiaJi Lin; BaoXi Shen; Tao Wang; XinYuan Sun; JiaWei Zheng; XiaoYan Zhu; DongHui Wu; FuPing Gu; HongGuo Li; YiKun Sun (Journal of Molecular Neuroscience, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Synergistic engineering of zincophilic sites and hierarchical porosity in lignin-derived carbon nanofiber networks for ultra-high energy density flexible zinc-ion hybrid capacitors - Lin-Xuan Wu; Bo Wang; Jia-Long Wen; Zhan-hui Yuan; Tong-Qi Yuan (Chemical Engineering Journal, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Bacterial and Fungal Communities Exhibit Different Assembly Process in Arid and Semi-arid Grasslands - Hui Li; Wenchang Ma; Mengyao Wu; Jiayuan Wei; Shuhui Liu; Lin Chen; Xuebin Li; Yinglong Chen; Danbo Pang (Journal of Soil Science and Plant Nutrition, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Monitoring photochemical reactions catalyzed by nano-titanium dioxide using electrospray laser desorption ionization mass spectrometry - Min-Zong Huang; Hsin-Hui Liang; Chi-Yang Lee; Shu-Yao Lin; Chun-Mei Wu; Jentaie Shiea (Analytica Chimica Acta, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Targeting complement and coagulation cascades with Buyang Huanwu Decoction attenuates acute inflammation and enhances neuroprotection in spinal cord injury - Dezun Ma; Xinyu Xie; Yijun Ma; Hui Yan; Haoyuan Yin; Xue Tan; Yan Li; Xinpei Lin; Yuexin Huang; Xiang Wu; Zhihao Zhou; Chenglin Yang; et al. (Science China Life Sciences, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Lysosomal dysfunction contributes to lead (Pb) and high-fat diet (HFD)-induced neuronal apoptosis: A link with cathepsin B - Yongke Yuan; Mengchen Liu; Mengdi Zhai; Meijia Wu; Wenhui Zhang; Yongjuan Xin; Yue Ba; Yu Zhang; Lin Han; Lihua Gao; Hui Huang (NeuroToxicology, 2026)

Transcriptional activation of TcToll9 to exogenous bacteria in the larvae of Tribolium castaneum - Qiuying He; Shiyuan Li; Hui Lv; Ruixuan Lin; Xintong Wu; Jisheng Liu (Journal of Stored Products Research, 2026)

A bipolar membrane-driven proton self-supply strategy for the sustained and efficient electrosynthesis of Na2S2O4 from desulfurization byproduct - Yingxue Fu; Jun Wu; Hao Chen; Lin Wu; Zhujiang Wang; Yelin Zhu; Jiaqi Long; Zhipeng Tang; Fenghua Shen; Kaisong Xiang; Hui Liu (Chemical Engineering Journal, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Diverse metamorphic P‒T‒t paths of the Mogutai tectono-metamorphic mélange, eastern Paleozoic Dunhuang Orogenic Belt, northwestern China - Yan-Lin Zhao; Yichao Chen; Xue-Li Jia; Hui C.G. Zhang; Zhen M.G. Li; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

High-fat diet-induced obesity-related hypertension via altered gut microbiota-mediated histone butyrylation - Hui Wang; Yuting Wang; Haojie Wu; Chen Shen; Yaqi Li; Baoling Bai; Xiaodong Sun; Yanyan Liu; Qin Zhang; Lin Shi (Science China Life Sciences, 2026)

Epidemiological characteristics of Chlamydial infection in hospitalized children in China: A nationwide retrospective study - Huiwen Zheng; Xinyu Wang; Xirong Wu; Yajie Guo; Feina Li; Jing Xiao; Hui Qi; Weiwei Jiao; Guoshuang Feng; Ju Yin; Lin Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

ASSR-mediated sludge yield reduction couples deterministic enrichment of Nitrospira with metabolic resource partitioning - Huanzhong Deng; Junling Yang; Ruohong Li; Kewen Li; Hui Lu; Bing Lin; Xingquan Xu; Jiajun Liao; Congrong Ye; Jie Deng; Bo Wu; Lianpeng Sun (Water Research, 2026)

CoFe2O4/Sepiolite as a heterogeneous catalyst for peroxymonosulfate activation: Efficient tetracycline degradation, mechanism, pathway, and toxicity assessment - Rui Li; Xiaolong Hu; Kexin Wu; Runa Hou; Mengxiang Hui; Bohao Liu; Junying Song; Li Wang; Qingbin Guo; Dengzheng Gao; Qingbiao Wang; Lin Li (Journal of Water Process Engineering, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Fine-tuned Ce electron density directs H2O2 activation pathway in industrially employable CeO2 nanozymes for ∼100% specificity and boosted activity in (Bromo)peroxidase mimicking - Tianqi Cheng; Bo Yuan; Chao Zhao; Zicong Tan; Xinyu Wu; Jian Lin Chen; Juan Liu; Yufei Zhao; Hui Wei; Yung-Kang Peng (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Dexmedetomidine Mitigates Sevoflurane-Induced Neurodevelopmental Effects in Paediatric Anaesthesia: A Meta-Analysis and Preclinical Study - Hsuan-Chih Lao; Chia-Wei Huang; Ssu-Han Wang; Yen-Lin Su; Chien-Hui Chang; Cheng-Yen Liao; Jen-Chieh Wu; Ying-Chun Lin; Jin-Wu Tsai (Journal of Neuroimmune Pharmacology, 2026)
Sevoflurane (Sevo) anaesthesia in children is linked to an increased incidence of postoperative emergence agitation (EA) and potential neurotoxicity in developing brains. However, the specific risks of subanaesthetic foetal or neonatal exposure to Sevo remain unclear. This study evaluates the safety and efficacy of combining dexmedetomidine (Dex) with Sevo to manage EA in paediatric anaesthesia. A systematic review and meta-analysis of randomized controlled clinical trials involving children under 8 years old revealed that Dex significantly reduces EA incidence when administered via intravenous, perineural, and intranasal routes. Using in utero electroporation, we found that pregnant mice exposed to 2.5% Sevo at embryonic days 14.5 and 15.5 exhibited transient neuronal migration deficits, with 25% of neurons delayed in deeper cortical layers. However, these neurons migrated to the cortex by postnatal day 8. Neonatal mice exposed to 2.5% Sevo experienced a 10% reduction in dendritic spine density in adolescence, associated with impaired somatosensory function, as assessed by the Von Frey test. Remarkably, Dex pretreatment ameliorated these pathological and functional changes. Thus, foetal or neonatal Sevo exposure can delay neuronal migration and reduce dendritic spine density. Dex co-administration effectively mitigates these adverse outcomes, supporting its potential use in paediatric anaesthesia to protect developing brains. Graphical abstract

Coupled polyphosphate storage and DOP mobilization along estuarine gradients in the Pearl River Estuary - Xian-Yang Zhang; Feng-Xian Han; Jian-Ting Li; Jia-Xue Wu; Song-Hui Lu; Lin-Jian Ou (Marine Pollution Bulletin, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Synergy between monomer oxygen vacancies and oxygen vacancy clusters in MnO2 enables efficient catalytic decomposition of N2O - Hui Dang; Wanjun Zhao; Chengming Zhang; Ruifang Wu; Liangliang Zhang; Ke Zheng; Shize Hu; Xiangqian Lin; Aiping Jia; Zhenxing Ren; Yongzhao Wang; Yongxiang Zhao (Journal of Hazardous Materials, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Promotion of nitric oxide to ammonia via nickel species enhanced active hydrogen generation - Hui Liu; Lin Wu; Yingxue Fu; Zhujiang Wang; Jiaqi Long; Jing Yuan; Xinlei Wang; Jieyu Li; Jun Wu; Kaisong Xiang (Chemical Engineering Journal, 2026)

The chemotaxonomic significance of chemical constituents from Gynostemma pentaphyllum - Hou-Lin Peng; Man-Hui Yang; Wu-Di Zhai; Wen-Juan Li; Jing Liu; Yan Zhang (Biochemical Systematics and Ecology, 2026)

A Novel Algorithm for Optimizing Structure of In-Situ Supplementary Irrigation Device for Afforestation in Dryland - Bokun Jia; Sen Zhai; Lin Zhang; Lijie Liu; Yong Yang; Xufei Liu; Shoujun Wu; Xin Hui (Water Resources Management, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Greater contribution of amino sugars to soil organic carbon than glomalin along an elevation gradient in semi-arid mountains - Yaru Zhao; Mengyao Wu; Ansa Rebi; Lin Chen; Guangyao Shi; Hui Li; Xuebin Li; Jinxing Zhou; Danbo Pang; Geshere Abdisa Gurmesa (Applied Soil Ecology, 2026)

Regional geochemical prospecting for Li–Be rare earth deposits: A case study in Southern Xinjiang, China - Jingjing Gong; Lujun Lin; Jianweng Gao; Yingjie Gao; Hui Wu; Yong Li; Jianzhou Yang; Zhuang Duan; Zuohuai Yang; Shixin Tang (Applied Geochemistry, 2026)

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Frequency-domain linear potential analysis on the near-trapping of water waves in the square cylinder array - Ying-Chao Ma; Hao Shen; Zhi-Wei Song; Hui Yang; Hong-Fei Mao; Zhong-Bing Zhou; Guang-Lin Wu (Ocean Engineering, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Integrated metabolomics reveals immunomodulatory compounds in giant African snail (Achatina fulica) extracts for the giant river prawn (Macrobrachium rosenbergii) - Youshang Lin; Chen-Hsun Liu; Chiu-Hui Kuo; Bonien Chen; Wei-Ming Wu; Tsung-Meng Wu; Te-Yu Liao; Kuohsun Chiu (Fish & Shellfish Immunology, 2025)

Synergistic exposure to endocrine-disrupting chemicals in pediatric lungs: Epidemiological drivers and disease-associated variations - Chunzhao Chen; Jie Yu; Hui Qi; Cuiying Zhong; Jian Tang; Chenghao Chen; Zheng Li; Xuemei Yang; Yujia Wu; Wanning Chen; Gang Yu; Lin Sun (Environmental Pollution, 2025)

HFPO-TA induces liver damage and ferroptosis in zebrafish by disrupting iron metabolism homeostasis - Lin Cheng; Zhonghua Fan; Yu Zhang; Xu Fang; Yuanyuan Wu; Hongru Liu; Lanxi Ye; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Multiple Mechanisms and Therapeutic Strategies for the Involvement of AMPK in the Development of Alzheimer’s Disease - Lin Yu; Xue Yang; Hui-Ping Lei; Yue-Ting Hu; Ling-Nan Wu; Shao-Yu Zhou; Feng Jin (Molecular Neurobiology, 2025)

A new perspective on endometriosis: Integrating eQTL mendelian randomization with transcriptomics and single-cell data analyses - Sheng Dou; Yi Wei; Zongyun Lin; Hui Wu; Fenglian Yang; Xuechang Cen; Wenjing Lu; Haimei Qin; Rong Wang; Junli Wang (Functional & Integrative Genomics, 2025)
Endometriosis is caused by the migration of endometrial cells to locations outside the uterine lining. Despite the increasing prevalence of endometriosis, there has been limited research on genetic effects, and its molecular mechanisms remain unclear. This study aimed to investigate the mechanisms underlying the development of endometriosis and to identify new genetic targets for endometriosis by integrating data from gene chips, single-cell mapping, and genome-wide association study databases. Using the Gene Expression Omnibus database, we downloaded data on normal endometrium, eutopic endometrium, and ectopic lesion tissues to explore the differentially expressed genes (DEGs) between normal and eutopic endometrium, and between eutopic and ectopic endometrium. Assessment of the relationships between DEGs and endometriosis involved differential expression, expression quantitative trait loci (eQTL), and Mendelian randomization (MR) analyses. Two single-cell atlas datasets were then analyzed to explore the mechanisms underlying disease development and progression. Intersection of MR results with DEGs between normal and eutopic endometrium highlighted 28 candidate biomarker genes (17 upregulated and 11 downregulated). Similarly, we identified two additional candidate biomarker genes by intersecting the DEGs between eutopic and ectopic endometrium with MR results. Among these 30 candidates, further filtering using single-cell datasets revealed that the histamine N-methyltransferase ( HNMT ), coiled-coil domain containing 28 A ( CCDC28A ), fatty acid desaturase 1 ( FADS1 ) and mahogunin ring finger 1 ( MGRN1 ) genes were differentially expressed between the normal and eutopic groups, consistent with transcriptomic and MR results. Our findings suggested that eutopic endometrium exhibits epithelial-mesenchymal transition (EMT). Cell communication analysis focused on ciliated epithelial cells expressing CDH1 and KRT23 revealed that, in the eutopic endometrium, ciliated epithelial cells are strongly correlated and interact with natural killer cells, T cells, and B cells. We identified four novel biomarker genes and found evidence for EMT in the eutopic endometrium. The mechanism of endometriosis progression may be closely related to EMT and changes in the immune microenvironment triggered by damage to ciliated epithelial cells.

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Numerical study of wave heights impact on the extreme wave attenuation characteristics of plants - Jinbo Lin; Runzhen Wu; Yanli He; Hui Yang; Yang Liu; Hongfei Mao; Guanglin Wu (Ocean Engineering, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

HFPO-TA exposure triggers hepatomegaly and lipid peroxidation via Nrf2/keap1 antioxidant dysregulation and ferroptosis activation in the liver - Xu Fang; Zhonghua Fan; Mengjiao Li; Zhi Li; Lin Cheng; Yuanyuan Wu; Li Wang; Hui Liu (Chemico-Biological Interactions, 2025)

Soil gas geochemical prospecting for deep mineral exploration: A case study of covered deposits on the southern Tibet Plateau - Gao-Xin Li; You-ye Zheng; Khan Junaid; Xin Chen; Jian-Hui Wu; Feng Gao; De-Cai Lin; Yong Zhang (Applied Geochemistry, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

Bond-oriented selective hydrogenation of unsaturated aldehyde by the tailoring of electronic metal-support interaction - Lin Ai; Peidong Li; Hui Ding; Yutong Jiao; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2025)

Flexible supercapacitors with biomass-derived nitrogen-functionalized few-layer carbon for wireless energy harvesting and management - Dayong Ren; Peihao Yang; Jiaqi Wang; Zhengxiang Song; Pengyue Wu; Zhanqiang Liu; Tianquan Lin; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Defense strategy of a pioneer plant (Miscanthus floridulus) under multi-heavy metal risks: Above- and below-ground tradeoff - Ruifang Jiao; Bohan Wu; Xiao Li; Shukun Lin; Kashif Hussain; Hui Liu (Plant and Soil, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Unveiling grape seed extract phytochemical composition, antioxidant, and immunostimulant action mechanisms in Caenorhabditis elegans and Drosophila melanogaster - Wenqi Huang; Shiye Lin; Xincheng Wu; Haoming Wu; Shengxiong Chen; Hui Cao; Jianbo Xiao (Food Bioscience, 2025)

Flash: Dual-gradient filtering membranes enable ultra-fast plasma separation - Xianchang Wu; Hui Niu; Tonghuan Zhan; Yulun Wu; Ping Qiao; Lin Hu; Bing Xu (Analytica Chimica Acta, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Low temperature hydrochar from sewage sludge enhancing polyacrylamide-based preformed particle gels with high temperature and salinity tolerance - Bei-Bei Wu; Yan-Yan Xu; Fan Gao; Ya-Jun Wu; Lin-Hui Xi; Zhi Kang; Hong-Kui He; Zu-Guo Yang; Zhi-Xiang Xu (Journal of Water Process Engineering, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Advanced materials for combined photodynamic and immunotherapy: Mechanisms and translational opportunities - Suizhi Zou; Kehua Hu; Xiaowan Guo; Lin-Lin Bu; Hui Qiu; Qiuji Wu (Chemical Engineering Journal, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Phenological growth stages and the extended BBCH scale for djulis (Chenopodium formosanum Koidz.) - Shu-Chung Wu; Chih-Chung Lin; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Diseases and Protection, 2025)

Simulation of the optical performance of a single corner cube retroreflector for the TianQin Project and lunar laser ranging stations - Zhizhao He; Hui Li; Xida Han; Xudong Lin; Xianlin Wu; Hongxiao Zhang; Ming Li (Advances in Space Research, 2025)

Bacillus amyloliquefaciens LY-1 culture broth enhances the storage properties of fresh litchi through acting on ROS metabolism - Hui Wang; Junhui Yuan; Yijing Wu; Yifan Wen; Yifen Lin; Yihui Chen; Hetong Lin (Food Chemistry, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Residential solar photovoltaic adoption: An in-depth review on potential, main barriers and related incentives - Jingwen Wu; Yanshan Zhang; Lin Zhu; Hui Li (Energy and Buildings, 2025)

Bisphenol AF induces lipid metabolism disorders, oxidative stress and upregulation of heat shock protein 70 in zebrafish - Bingya Zhang; Zhonghua Fan; Xuan Liu; Yuanyuan Wu; Lin Cheng; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Terpene and lignan glycosides from the leaves of Cyclocarya paliurus and their anti-inflammatory activity - Si-Yang Fang; Jia Liu; Chang-Jian Wu; Xing-Gui Zhang; Hui-Lin Dong; Dong-Jian Zhang; Can Hu; Jian Zhang; Ke Pan; Zhi-Qi Yin; Yan-Hua Qin; Lei Wang (Phytochemistry, 2025)

Numerical study on hydrodynamic performance of a trimaran in regular waves considering steady flow and shallow water effects - Bo Zhou; Zhifei Wu; Xiang Lin; Wenxin Yi; Hui Liu; Guiyong Zhang (Ocean Engineering, 2025)

DSSAT modeling of oilseed flax (Linum usitatissimum L.): Sensitivity analysis of yield to weather variability and nitrogen application - Zechen Lin; Yue Li; Gerrit Hoogenboom; Yuhong Gao; Bing Wu; Ling Wu; Lili Wu; Hui Zhou; Bin Yan; Peina Lu; Jie Tang; Shunchang Su; et al. (Field Crops Research, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Enterococcus faecalis Exerts Neuroprotective Effects via the Vagus Nerve in a Mouse Model of Parkinson’s Disease - Xian Shao; Tao Wu; Mengyun Li; Matao Zheng; Hui Lin; Xuchen Qi (Molecular Neurobiology, 2025)

Modeling and optimization of docosahexaenoic acid production by Schizochytrium sp. based on kinetic modeling and genetic algorithm optimized artificial neural network - Zi-Lei Chen; Hui Lian; Lin-Hui Yang; Yang Wu; Bo Ren; Dong-Sheng Guo (Bioresource Technology, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Transcriptome-based analysis reveals the toxic effects of perfluorononanoic acid by affecting the development of the cardiovascular system and lipid metabolism in zebrafish - Mingqing Qian; Weiqiang Sun; Lin Cheng; Yuanyuan Wu; Li Wang; Hui Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

High-affinity uric acid clearance based on motile β-CD/F-127 polyrotaxane microspheres for enhanced diabetic wound repair - Xinlin Jiang; Zipeng Wu; Xiaoru Tan; Yichen Lin; Hui Xing; Yinglin Xuan; Dong Ma; Xin Cui (Carbohydrate Polymers, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Morphology effect on the photocatalytic performance of CeO2 and insights into the degradation mechanism of tetracycline - Saisai Deng; Hui Wang; Yanmei Dong; Wenjing Cheng; Xiangang Lin; Longxia Wu; Jun Hu; Yuanxu Liu; Yangyang Li (Journal of Environmental Chemical Engineering, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

Synthetic biology meets Aspergillus: engineering strategies for next-generation organic acid production - Yang Wu; Qian-Hui Xu; Zi-Lei Chen; Lin-Hui Yang; Dong-Sheng Guo (World Journal of Microbiology and Biotechnology, 2025)

Establishment and application of novel transient cotyledon and seed transformation systems in Tartary buckwheat - Huala Wu; Hui Li; Jiayi Lin; Yujun Ouyang; Chenglei Li; Hongyou Li; Tao Wang; Qi Wu; Haixia Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Investigation of land subsidence in Guangdong Province, China, using PS-InSAR technique - Liangke Huang; Peijie Zhu; Tengxu Zhang; Lin He; Wenhao Wu; Zixuan Ge; Hui Ai (Advances in Space Research, 2025)

Jaranol alleviates cognitive impairment in db/db mice through the PI3K/AKT pathway - Ye Qian; Yue Xu; Qiuyu Zhang; Chengyu Huang; Hui Li; Lin Gao; Shidi Wu; Chengyu Qi; Xiangru Wen; Xiaoyan Zhou; Changjiang Ying (Metabolic Brain Disease, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Novel antibody- and aptamer-based approaches for sensitive detection of mycotoxin fusaric acid in cereal - Shih-Wei Wu; Chia-Yu Hsieh; Biing-Hui Liu; Xin-Jie Lin; Feng-Yih Yu (Food Chemistry, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

GWAS analysis revealed genomic loci and candidate genes associated with the 100-seed weight in high-latitude-adapted soybean germplasm - Javaid Akhter Bhat; Hui Yu; Lin Weng; Yilin Yuan; Peipei Zhang; Jiantian Leng; Jingjing He; Beifang Zhao; Moran Bu; Songquan Wu; Deyue Yu; Xianzhong Feng (Theoretical and Applied Genetics, 2025)

Epigenetic Modifications as Novel Therapeutic Strategies of Cancer Chemoprevention by Phytochemicals - Hui-Hsia Hsieh; Min-Zhan Kuo; I-An Chen; Chien-Ju Lin; Victor Hsu; Wei-Chun HuangFu; Tien-Yuan Wu (Pharmaceutical Research, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Nitrogen fixation of different seasons and parts of seagrass Enhalus acoroides in Xincun Bay, northern South China Sea - Zhen-Zhen Wu; Xiao-Mei Li; Hui Zhao; Long Wei; Jun-De Dong; Mei-Lin Wu (Regional Studies in Marine Science, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Experimental investigation on strength characteristics of marine soft clay under monotonic and cyclic loading - Lin Guo; Hao Wu; Yanping He; Hui Li; Yilong Sun (Marine Georesources & Geotechnology, 2024)

Higher resistance of larch-broadleaf mixed forests than larch forests against soil acidification under experimental nitrogen addition - Meixia Gao; Guigang Lin; Feifei Zhu; Zhou Wu; Per Gundersen; De-Hui Zeng; Erik A. Hobbie; Weixing Zhu; Yunting Fang (Plant and Soil, 2024)

The Associations of Urinary DEHP Metabolites in Pregnant Women with Serum Thyroid Hormone and Thyroid-Related Genes in Neonatal Umbilical Cord Blood in Jilin, China - Xueting Zhang; Wen Qi; Zihan Su; Hui Ye; Haotang Zhao; Jianwei Cui; Xiaoqi Fang; Liuwei Shi; Xueying Liu; Ziyu Wang; Hang Xu; Fuju Wu; et al. (Exposure and Health, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Applying kitchen compost promoted soil chrysene degradation by optimizing microbial community structure - Bing Kou; Lin Huo; Minyi Cao; Tingqiao Yu; Yuman Wu; Kunlong Hui; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Livestock grazing modes induced the rapid differentiation of community recruitment in alpine meadow - Hui Fang; Lingchao Meng; Zhiqiang Dang; Jingxue Zhao; Shixiong Li; Gao-Lin Wu (Ecological Engineering, 2024)

Interface-Confined nanocatalysts at hollow porous nanofibers for High-Performance cascaded remediation of radioactive wastewater - Qi-Hui Ye; Hao Ye; Yu-Cong Yu; Xiao-Lin Wang; Qiao Luo; Ming-Bang Wu; Juming Yao (Chemical Engineering Journal, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

Light attenuation parameterization in a highly turbid mega estuary and its impact on the coastal planktonic ecosystem - Qiyinan Lin; Zhixuan Feng; Yihe Wang; Xue Wang; Zhaoxuan Bian; Fan Zhang; Fang Cao; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2024)
Light is essential for phytoplankton photosynthesis and many other biogeochemical processes in the aquatic system. However, light regimes vary greatly in the estuaries and coasts due to the optical complexity of the Case-2 waters. In this study, observed vertical profiles of photosynthetically active radiation (PAR; 400-700 nm) in a highly turbid mega estuary, the Changjiang (Yangtze River) Estuary, are used to quantify the effects of sedimentary and biogeochemical components on PAR attenuation in the water column and associated ecological impacts. The in-situ data suggest suspended sediment plays the most crucial role in light diffuse attenuation coefficient (K d ) distribution, followed by salinity (i.e., an index for colored dissolved organic matter) and phytoplankton chlorophyll-a. A new parameterization of K d , based on suspended sediment, chlorophyll-a concentration, and salinity, is fitted using multiple linear regression. The previous and new K d parameterizations are further applied to a coupled hydrodynamics-sediment-ecosystem model to simulate spring phytoplankton blooms. Comparative model runs reveal that the new K d parameterization resulted in a better representation of the spring bloom patterns in magnitude, horizontal distribution, and vertical thickness of the high chlorophyll-a band offshore the turbidity maximum zone during the spring bloom. In summary, accurate representations of underwater light fields in the optically complex Case-2 water are critical in understanding biophysical processes that control planktonic ecosystem dynamics in the estuaries and coastal seas.

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Numerical study of energy consumption in spacer-filled feed channels through 3D inverse modeling and computational fluid dynamics - Hui Guan; Jiacheng Li; Doufeng Wu; Sanchuan Yu; Peifeng Lin; Xiao Hu (Desalination, 2024)

Extremely large Cl isotopic fractionation in Chang'e-5 impact glass beads - Yue Zhang; Hejiu Hui; Sen Hu; Jialong Hao; Ruiying Li; Wei Yang; Qiuli Li; Yangting Lin; Xianhua Li; Fuyuan Wu (Earth and Planetary Science Letters, 2024)

Enhancing plant fiber antibacterial and antiviral performance through synergistic action of amino and sulfonic acid groups - Jinxin Lan; Yao Wu; Jiazhen Chen; Peng Wang; Hui Chen; Jinfeng Huang; Dongdong Lu; Changmei Lin; Xiaojuan Ma; Shilin Cao (Carbohydrate Polymers, 2024)

Map-based cloning of LPD, a major gene positively regulates leaf prickle development in eggplant - Changjiao Ke; Wenxiang Guan; Jialong Jiang; Likun Huang; Hui Li; Wenjing Li; Yanyu Lin; Lihui Lin; Xiaofang Xie; Weiren Wu; Wenxia Gao; Yan Zheng (Theoretical and Applied Genetics, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Zn2+ chelating peptide GFLGSP: Characterization of structure/Zn2+ chelating mode and the potential mechanisms for promoting Zn2+ transport in Caco-2 cells - Shanting Lin; Jun Li; Xiao Hu; Shengjun Chen; Hui Huang; Yanyan Wu; Zhenxing Li (Food Research International, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Fast-track development of an automated solar photovoltaic module detecting framework utilizing open-access multispectral satellite imagery - Pei-Cheng Wu; Meng-Chi Hung; Ruey-Shing Lin; Shu-Yen Huang; Zhao-Hui Lin (Remote Sensing Applications: Society and Environment, 2024)

Achieving efficient power generation for an enclosed drifting buoy by multi-DOF wave energy harvesting - LiGuo Wang; Jing Lin; Hui Li; JunChuan Jiang; ShiXuan Wu; GuanYu Lu (Ocean Engineering, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

A novel approach for sludge deep-dewatering via flowing-out enhancement but not relying on cell lysis and bound water release - Hao Zhang; Wen-Hui Liu; Yun-Yan Gao; Ping Sun; Yuan-Ping Zeng; Lin-Lin Ma; Jiang-Nan Wu; Shun-Gui Zhou; Xi-Qin Cui; Raymond Jianxiong Zeng; Hou-Feng Wang (Water Research, 2024)

Complete long-term monitoring of greenhouse gas emissions from a full-scale industrial wastewater treatment plant with different cover configurations - Qinyi Wang; Yangyue Sheng; Yili Zhang; Xinrun Zhong; Hui Liu; Zhengfeng Huang; Dan Li; Hao Wu; Yuanzhi Ni; Junqi Zhang; Weiqing Lin; Kaipei Qiu; et al. (Journal of Environmental Management, 2024)

Synthesis of stable mesoporous Zr-MOFs using pyrazine-containing ligand for efficient capture of Pb(II) in wastewater - Lixiang Liu; Laidi Wu; Yue Chen; Yongfei Ma; Li Lin; Shuo Li; Xiujuan Yang; Hui Chen; Guojian Duan (Journal of Environmental Chemical Engineering, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Self-supporting high-entropy Co-Cr-Fe-Ni-Nb oxide electrocatalyst with nanoporous structure for oxygen evolution reaction - Yuhan Lin; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Shuilin Wu; Zhenduo Cui; Huaijun Sun; Huifang Zhang; Shengli Zhu (Chemical Engineering Journal, 2024)

Heavy metal spatial distribution, source analysis, and ecological risks in the central hilly area of Hainan Island, China: results from a high-density soil survey - Jingjing Gong; Jianweng Gao; Hui Wu; Lujun Lin; Jianzhou Yang; Shixin Tang; Zhengliang Wang; Zhuang Duan; Yangang Fu; Yongwen Cai; Shuqi Hu; Yong Li (Environmental Geochemistry and Health, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Corrigendum to “Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases” [Sci. Total Environ. 925 171492] - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Effects and mechanisms of polycyclic aromatic hydrocarbons in inflammatory skin diseases - Hui Jin; Ziyuan Lin; Tianyi Pang; Jingwen Wu; Cheng Zhao; Ying Zhang; Yu Lei; Qilin Li; Xu Yao; Ming Zhao; Qianjin Lu (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Exercise-induced microbial changes in preventing type 2 diabetes - Ting Yao; Hui Wang; Kaiqing Lin; Ruwen Wang; Shanshan Guo; Peijie Chen; Hao Wu; Tiemin Liu; Ru Wang (Science China Life Sciences, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Improving time-series InSAR deformation estimation for city clusters by deep learning-based atmospheric delay correction - Peifeng Ma; Chang Yu; Zeyu Jiao; Yi Zheng; Zherong Wu; Wenfei Mao; Hui Lin (Remote Sensing of Environment, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Plasmonic array assisted mass spectrometry for preferential metabolite detection - Xvelian Li; Wei Chen; Mengyi Wu; Wenjun Yu; Mengfei Wang; Minjia Niu; Fanyu Meng; Yuewei Zhao; Ahmed Osman; Nahla O. Mousa; Hui Shi; Kun Qian; et al. (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Potential dietary calcium supplement: Calcium-chelating peptides and peptide-calcium complexes derived from blue food proteins - Shanting Lin; Jun Li; Xiao Hu; Shengjun Chen; Hui Huang; Yanyan Wu; Zhenxing Li (Trends in Food Science & Technology, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Association between blood arsenic concentration and dyslipidemia: Mediating effect of lipid peroxidation in the elderly - Jia-Hui Huang; Yi Wu; Wei He; Jun-Xian Wang; Lin Fu; Xi Chen (Journal of Trace Elements in Medicine and Biology, 2024)

Mechanisms of low cadmium accumulation in crops: A comprehensive overview from rhizosphere soil to edible parts - Lihong Lin; Xinyue Wu; Xingying Deng; Zheng Lin; Chunguang Liu; Jiexiang Zhang; Tao He; Yunqiang Yi; Hui Liu; Yifan Wang; Weimin Sun; Zhimin Xu (Environmental Research, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Insight into the flame-retardant mechanism of different organic-modified layered double hydroxide for epoxy resin - Xiao-Hui Shi; Xue-Lin Li; Hong Shi; Qing-Yun Liu; Wei-Min Xie; Shi-Jie Wu; Nan Zhao; De-Yi Wang (Applied Clay Science, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Late Neolithic to Bronze Age water management and upland rice cultivation in the mountainous areas of Southeastern China Coast - Guiping Wu; Xinxin Zuo; Wei Wu; Lin Ren; Chunming Wu; Yingjun Lin; Hui Xie; Yaoyao Pei; Guiyu Zhou (Quaternary International, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Differential roles of anthropogenic CO2 in mediating seasonal amplitudes of ocean acidification metrics over a coastal coral habitat - Xu Dong; Di Qi; Baohong Chen; Yingxu Wu; Xinqing Zheng; Hui Lin (Journal of Marine Systems, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Isolation, identification of antioxidant peptides from earthworm proteins and analysis of the structure–activity relationship of the peptides based on quantum chemical calculations - Ping He; Yi Zhang; Yizhe Zhang; Lina Zhang; ZhengLi Lin; Chongzhen Sun; Hui Wu; Mengmeng Zhang (Food Chemistry, 2024)

Exosomal derived miR-1246 from hydroquinone-transformed cells drives S phase accumulation arrest by targeting cyclin G2 in TK6 cells - Yuting Chen; Lin Chen; Shiheng Zhu; Hui Yang; Zhongming Ye; Huanhuan Wang; Haipeng Wu; Yao Wu; Qian Sun; Xiaoshan Liu; Hairong Liang; Huanwen Tang (Chemico-Biological Interactions, 2024)

The mediating effect of perceived stress on the relationship between big five personality traits and suboptimal health status in Chinese population: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Qihua Guan; Hualei Dong; Zhihui Zhang; Zheng Guo; Zi Lin; Hui Niu; Yibo Wu; Haifeng Hou (EPMA Journal, 2023)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Sustainable development of World Cultural Heritage sites in China estimated from optical and SAR remotely sensed data - Fulong Chen; Huadong Guo; Peifeng Ma; Yunwei Tang; Fan Wu; Meng Zhu; Wei Zhou; Sheng Gao; Hui Lin (Remote Sensing of Environment, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Immunomodulatory effect of earthworm protein autolysates on Cyclophosphamide(CTX)-Induced immunosuppressed mice - Yizhe Zhang; Ping He; Leiman Pan; Zhengli Lin; Jinxi Yang; Hui Wu; Mengmeng Zhang (Food Bioscience, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Predicting 1-, 3-, 5-, and 8-year all-cause mortality in a community-dwelling older adult cohort: relevance for predictive, preventive, and personalized medicine - Yequn Chen; Xiulian Deng; Dong Lin; Peixuan Yang; Shiwan Wu; Xidong Wang; Hui Zhou; Ximin Chen; Xiaochun Wang; Weichai Wu; Kaibing Ke; Wenjia Huang; et al. (EPMA Journal, 2023)
Background Population aging is a global public health issue involving increased prevalence of age-related diseases, and concomitant burden on medical resources and the economy. Ninety-two diseases have been identified as age-related, accounting for 51.3% of the global adult disease burden. The economic cost per capita for older people over 60 years is 10 times that of the younger population. From the aspects of predictive, preventive, and personalized medicine (PPPM), developing a risk-prediction model can help identify individuals at high risk for all-cause mortality and provide an opportunity for targeted prevention through personalized intervention at an early stage. However, there is still a lack of predictive models to help community-dwelling older adults do well in healthcare. Objectives This study aims to develop an accurate 1-, 3-, 5-, and 8-year all-cause mortality risk-prediction model by using clinical multidimensional variables, and investigate risk factors for 1-, 3-, 5-, and 8-year all-cause mortality in community-dwelling older adults to guide primary prevention. Methods This is a two-center cohort study. Inclusion criteria: (1) community-dwelling adult, (2) resided in the districts of Chaonan or Haojiang for more than 6 months in the past 12 months, and (3) completed a health examination. Exclusion criteria: (1) age less than 60 years, (2) more than 30 incomplete variables, (3) no signed informed consent. The primary outcome of the study was all-cause mortality obtained from face-to-face interviews, telephone interviews, and the medical death database from 2012 to 2021. Finally, we enrolled 5085 community-dwelling adults, 60 years and older, who underwent routine health screening in the Chaonan and Haojiang districts, southern China, from 2012 to 2021. Of them, 3091 participants from Chaonan were recruited as the primary training and internal validation study cohort, while 1994 participants from Haojiang were recruited as the external validation cohort. A total of 95 clinical multidimensional variables, including demographics, lifestyle behaviors, symptoms, medical history, family history, physical examination, laboratory tests, and electrocardiogram (ECG) data were collected to identify candidate risk factors and characteristics. Risk factors were identified using least absolute shrinkage and selection operator (LASSO) models and multivariable Cox proportional hazards regression analysis. A nomogram predictive model for 1-, 3-, 5- and 8-year all-cause mortality was constructed. The accuracy and calibration of the nomogram prediction model were assessed using the concordance index (C-index), integrated Brier score (IBS), receiver operating characteristic (ROC), and calibration curves. The clinical validity of the model was assessed using decision curve analysis (DCA). Results Nine independent risk factors for 1-, 3-, 5-, and 8-year all-cause mortality were identified, including increased age, male, alcohol status, higher daily liquor consumption, history of cancer, elevated fasting glucose, lower hemoglobin, higher heart rate, and the occurrence of heart block. The acquisition of risk factor criteria is low cost, easily obtained, convenient for clinical application, and provides new insights and targets for the development of personalized prevention and interventions for high-risk individuals. The areas under the curve (AUC) of the nomogram model were 0.767, 0.776, and 0.806, and the C-indexes were 0.765, 0.775, and 0.797, in the training, internal validation, and external validation sets, respectively. The IBS was less than 0.25, which indicates good calibration. Calibration and decision curves showed that the predicted probabilities were in good agreement with the actual probabilities and had good clinical predictive value for PPPM. Conclusion The personalized risk prediction model can identify individuals at high risk of all-cause mortality, help offer primary care to prevent all-cause mortality, and provide personalized medical treatment for these high-risk individuals from the PPPM perspective. Strict control of daily liquor consumption, lowering fasting glucose, raising hemoglobin, controlling heart rate, and treatment of heart block could be beneficial for improving survival in elderly populations.

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Assessment of microplastic contamination in an eastern Pacific tuna (Katsuwonus pelamis) and evaluation of its health risk implication through molecular docking and metabolomics studies - Lijun Wu; Xiaojie Dai; Jing Xu; Danyun Ou; Lei Wang; Hui Lin; Weiyi He; Haitao Lin; Rupeng Du; Hao Huang; Weiwen Li; Zhong Pan (Food Chemistry, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Three new hasubanan-type alkaloids from the Stephania longa - Rong-Xiao Lin; Lixia Fan; Xin Chen; Jundi Wu; Zheng Liu; Fang Liu; An-Ping Yang; Chenglai Xia; Hui Liu; Hong-Yuan Chen (Natural Product Research, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Ambient air pollution associated with incident asthma, subsequent cardiovascular disease and death: A trajectory analysis of a national cohort - Xiaojie Wang; Shanshan Ran; Hui Xia; Hui Shi; Gan Wu; Zilong Zhang; Chongjian Wang; Miao Cai; Junguo Zhang; Hualiang Lin (Journal of Hazardous Materials, 2023)

Prevalence of antimicrobial resistance in a full-scale drinking water treatment plant - Qihui Gu; Tao Lin; Xianhu Wei; Youxiong Zhang; Shi Wu; Xiaojuan Yang; Hui Zhao; Chufang Wang; Juan Wang; Yu Ding; Jumei Zhang; Qingping Wu (Journal of Environmental Management, 2023)

Isolation, identification, and structure-activity relationship of novel ACE inhibitory peptides from earthworm protein in vitro gastrointestinal digestion product - Zhengli Lin; Hui Wu; Mengmeng Zhang (Food Bioscience, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Twisting two-dimensional photothermal sponges for boosting solar steam generation - Feng Lu; Shao-Lin Wu; Lu-Na Quan; Zhi-Hui Zhong; Hao-Cheng Yang; Ming Xue (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Ketamine exerts dual effects on the apoptosis of primary cultured hippocampal neurons from fetal rats in vitro - Guo-Hua Wu; Que-Hui Guo; Xiao-Dong Xu; Jian-Chang Lin; Gui-Ting You; Cai-Hou Lin; Liang-Cheng Zhang (Metabolic Brain Disease, 2023)

An "ON-OFF" fluorescent sensor based on a novel zinc-based flower-like structured metal-organic framework for sequential detection of deferasirox and tigecycline - Xiaowen Xu; Hui Lin; Bixia Lin; Lingyi Huang; Pingping Wu; Youjia Wu; Liying Huang (Analytica Chimica Acta, 2023)

A deep learning-based method for detecting granular fertilizer deposition distribution patterns in centrifugal variable-rate spreader fertilization - Hui Liu; Lin Wang; Yinyan Shi; Xiaochan Wang; Feilong Chang; Yao Wu (Computers and Electronics in Agriculture, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Theoretical study on stability evolution of soft and hard interbedded bedding reservoir slopes - Qiong Wu; Bo Zhang; Hui-ming Tang; Di Wang; Zhi-qi Liu; Zhi-wei Lin (Journal of Mountain Science, 2023)

Climate change-induced shrub encroachment changes soil hydraulic properties and inhibits herbaceous growth in alpine meadows - Yi-Fan Liu; Hui Fang; Jianjun Shi; Pedro A M Leite; Jingxue Zhao; Gao-Lin Wu (Agricultural and Forest Meteorology, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Biogeographic distribution, ecotype partitioning and controlling factors of Chloroflexi in the sediments of six hadal trenches of the Pacific Ocean - Jiaxin Wu; Li Wang; Jiangtao Du; Yuheng Liu; Lin Hu; Hui Wei; Jiasong Fang; Rulong Liu (Science of The Total Environment, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Editorial: Macroecology of coastal zones under global changes - Meilin Wu; Hui Zhao; Qiuying Han; Lin Hui; Vetrimurugan Elumalai; Luzhen Chen; Keerthi Sri Senarathna Atapaththu (Frontiers in Marine Science, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Warming-driven indirect effects on alpine grasslands: short-term gravel encroachment rapidly reshapes community structure and reduces community stability - Gao-Lin Wu; Hui Fang; Zeng Cui; Jingxue Zhao (Oecologia, 2023)

Microplastics may act as a vector for potentially hazardous metals in rural soils in Xiamen, China - Rupeng Du; Yufang Wu; Haitao Lin; Jincheng Sun; Weiwen Li; Zhong Pan; Shaojian Zeng; Qi Chen; Jinjing Luo; Hui Lin (Journal of Soils and Sediments, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Automatic detection and classification of land subsidence in deltaic metropolitan areas using distributed scatterer InSAR and Oriented R-CNN - Zherong Wu; Peifeng Ma; Yi Zheng; Feng Gu; Lin Liu; Hui Lin (Remote Sensing of Environment, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Machine learning exploration of the mobility and environmental assessment of toxic elements in mining-associated solid wastes - Chongchong Qi; Mengting Wu; Hui Liu; Yanjie Liang; Xueming Liu; Zhang Lin (Journal of Cleaner Production, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A concise synthesis of marine natural product (−)-15-oxopuupehenol from (+)-sclarelide - Yun-Fei Cheng; Hui-Jing Li; Yin-Lin Zhang; Yan-Chao Wu (Natural Product Research, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Preparation of photocatalysts decorated by carbon quantum dots (CQDs) and their applications: A review - Feixia Zhao; Xueying Li; Mingxing Zuo; Yunshan Liang; Pufeng Qin; Hui Wang; Zhibin Wu; Lin Luo; Chao Liu; Lijian Leng (Journal of Environmental Chemical Engineering, 2023)

Genome-based risk assessment for foodborne Salmonella enterica from food animals in China: A One Health perspective - Biao Tang; Abubakar Siddique; Chenhao Jia; Abdelaziz Ed-Dra; Jing Wu; Hui Lin; Min Yue (International Journal of Food Microbiology, 2023)

Screening, ACE-inhibitory mechanism and structure-activity relationship of a novel ACE-inhibitory peptide from Lepidium meyenii (Maca) protein hydrolysate - Zhengli Lin; Junwen Lai; Ping He; Leiman Pan; Yizhe Zhang; Mengmeng Zhang; Hui Wu (Food Bioscience, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Colletotrichum species causing anthracnose disease on avocado fruit in Taiwan - Chao-Jung Wu; Miao-Chun Lin; Hui-Fang Ni (European Journal of Plant Pathology, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Dynamic change of oligopeptides and free amino acids composition in five types of tea with different fermentation degree processed from the same batch of fresh tea (Camelilia Sinensis. L.) leaves - Feng Zhao; Wenxi Wu; Chi Wang; Xiaojuan Wang; Hui Liu; Jiang Qian; Chunping Cai; Yong Xie; Yu Lin (Food Chemistry, 2023)

Shrub encroachment increases soil erosion risk in hillside alpine meadows of the Qinghai-Tibetan Plateau, NW China - Yi-Fan Liu; Hui Fang; Ze Huang; Pedro A.M. Leite; Yu Liu; Manuel López-Vicente; Jingxue Zhao; Zhi-Hua Shi; Gao-Lin Wu (CATENA, 2023)

Cross-species binding spectrum of ACE2 to SARS-CoV-2 RBD - Xihao Liao; Changge Guan; Chenghua Wang; Xinjie Chen; Xiaomei Lin; Lianghua Lu; Lu Li; Ting Wang; Nan Su; Bian Wu; Xinquan Wang; Chong Zhang; et al. (Science China Life Sciences, 2023)

Seasonal variation of population and individual dietary niche in the avivorous bat, Ia io - Lixin Gong; Hao Gu; Yang Chang; Zhiqiang Wang; Biye Shi; Aiqing Lin; Hui Wu; Jiang Feng; Tinglei Jiang (Oecologia, 2023)

Gravity disturbance compensation for dual-axis rotary modulation inertial navigation system - Panpan Zhang; Lin Wu; Lifeng Bao; Bo Wang; Hui Liu; Qianqian Li; Yong Wang (Frontiers in Marine Science, 2023)
Gravity disturbance compensation is an important technique for improving the positioning accuracy of high-precision inertial navigation systems (INS). Aiming at the current problems of the resolution of gravity compensation background field and the robustness of gravity compensation algorithm are insufficient for gravity compensation. In this study, the error and frequency characteristics of INS caused by gravity disturbances are investigated. The gravity disturbance with a spatial resolution of 1’ × 1’ from a high-precision satellite altimetry marine gravity field model is preliminarily introduced into the initial alignment and pure INS calculation to implement the gravity compensation of the dual-axis rotary modulation INS. Detailed calculation results show that the east gravity disturbance affects the north attitude, and the north gravity disturbance affects the east attitude in the initial alignment. In the pure INS calculation, the horizontal gravity disturbance causes a navigation error in the form of Schuler oscillation. The INS navigation error caused by horizontal gravity disturbance is mainly affected by its amplitude; however, the horizontal gravity disturbance accuracy from the satellite altimetry model for INS gravity compensation can be ignored in practice. In addition, for low-speed underwater vehicles, the influence of high-frequency gravity disturbance signals on the INS position shows an increasing trend. Finally, the effectiveness of the gravity compensation achieved by the horizontal gravity disturbance from the satellite altimeter model is confirmed by a dynamic shipborne test. The positioning accuracy of the rotary modulation INS is maximally improved by approximately 17.9% after the horizontal gravity disturbance is compensated simultaneously in the pure INS calculation and the initial alignment.

Cobalt exposure and dyslipidemia in elderly population: the mediating role of systemic inflammation and lipid peroxidation - Jia-Hui Huang; Li Tao; Yi Wu; Wei He; Jun-Xian Wang; Xi Chen; Lin Fu (Environmental Science and Pollution Research, 2023)

Dam construction alters planktonic microbial predator‒prey communities in the urban reaches of the Yangtze River - Qiaojuan Wang; Junwen Chen; Weixiao Qi; Donglin Wang; Hui Lin; Xinghua Wu; Dianchang Wang; Yaohui Bai; Jiuhui Qu (Water Research, 2023)

Simulating future land use by coupling ecological security patterns and multiple scenarios - Wenbin Nie; Bin Xu; Fan Yang; Yan Shi; Bintao Liu; Renwu Wu; Wei Lin; Hui Pei; Zhiyi Bao (Science of The Total Environment, 2023)

Environmental laws and ecological restoration projects enhancing ecosystem services in China: A meta-analysis - Tao Liu; Le Yu; Xin Chen; Hui Wu; Hui Lin; Chengxiu Li; Jiaru Hou (Journal of Environmental Management, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

One-step coaxial spinning of core-sheath hydrogel fibers for stretchable ionic strain sensors - Hui Wu; Lin Wang; Hengyi Lou; Junmin Wan; Xiong Pu (Chemical Engineering Journal, 2023)

A gas permeable membrane electrode for selective and durable H2S production from SO2 - Hui Liu; Xudong Liu; Zhujiang Wang; Huimin Yi; Yingxue Fu; Lin Wu; Fenghua Shen; Pingshan Wang; Min Liu; Zhang Lin; Kaisong Xiang; Liyuan Chai (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Two new chromones and a new coumarin from the fruit of Cnidium monnieri (L.) Cusson - Hui-Chi Huang; Chun-Hsiang Lin; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Che-Yi Chao; Guan-Jhong Huang; Yueh-Hsiung Kuo (Natural Product Research, 2023)

Evaluating the release and metabolism of ricinine from castor cake fertilizer in soils using a LC-QTOF/MS coupled with SIRIUS workflow - Kai-Xuan Zheng; Cheng-Hua Liu; Sichao Wang; Yu-Min Tzou; Chih-Min Chiang; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Ya-Hui Chuang (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Soil organic carbon content increase in the east and south of China is accompanied by soil acidification - Xiao-Lin Sun; Budiman Minasny; Yun-Jin Wu; Hui-Li Wang; Xiao-Hui Fan; Gan-Lin Zhang (Science of The Total Environment, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Vanadium isotope evidence for widespread marine oxygenation from the late Ediacaran to early Cambrian - Wei Wei; Xi Chen; Hong-Fei Ling; Fei Wu; Lin-Hui Dong; Songqi Pan; Zhenhua Jing; Fang Huang (Earth and Planetary Science Letters, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Electron transfer-based peroxydisulfate activation by waste herb residue biochar: Adsorption versus surface oxidation - Xuantong Chen; Zhen Guo; Juemiao Liu; Fei Wu; Cheng Cheng; Heng Lin; Wei Ren; Hui Zhang (Chemical Engineering Journal, 2023)

Linolenic acid conjugated chitosan micelles for improving the oral absorption of doxorubicin via fatty acid transporter - Yuhan Yang; Yangyi Chen; Dianpeng Li; Shiyuan Lin; Hui Chen; Wei Wu; Wei Zhang (Carbohydrate Polymers, 2023)

Polycyclic aromatic hydrocarbons in surface water and sediment from Shanghai port, China: spatial distribution, source apportionment, and potential risk assessment - Hui Zhang; Lin Yuan; Junzeng Xue; Huixian Wu (Environmental Science and Pollution Research, 2023)

A symbiosis between Euploea butterflies and yeasts - Wan-Rou Lin; Yi-Ping Chang; Hui-Lin Wu; I-Cheng Hsu; Pi-Han Wang (Symbiosis, 2023)

Associations of trace element levels in paired serum, whole blood, and tissue: an example of esophageal squamous cell carcinoma - Kexin Cao; Jingbing Zhang; Geng Wang; Xiaosheng Lin; Fulan Zhan; Kusheng Wu; Wei Tan; Hui Geng; Caixia Liu (Environmental Science and Pollution Research, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Breast cancer incidence in a national cohort of female workers exposed to special health hazards in Taiwan: a retrospective case-cohort study of ~ 300,000 occupational records spanning 20 years - Yun-Shiuan Chuang; Chun-Ying Lee; Pei-Chen Lin; Chih-Hong Pan; Hui-Min Hsieh; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2022)

Microfossil evidence of rice cultivation on the Southeast China Coast 7500 years ago - Xinxin Zuo; Jinqi Dai; Wei Wu; Jianhui Jin; Wei Ge; Yinping Wang; Lin Ren; Yingjun Lin; Yaoyao Pei; Hui Xie (Science China Earth Sciences, 2022)

Insulin growth factor-1 enhances proliferation and inhibits apoptosis of neural progenitor cells by phosphorylation of Akt/mTOR/p70S6K molecules and triggering intrinsic apoptosis signaling pathway - Bo Zhang; Lingyun Hu; Jianying Zhang; Hui Wu; Wei Li; Lin Gou; Hao Liu (Cell and Tissue Banking, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Long-term exercise pre-training attenuates Alzheimer’s disease–related pathology in a transgenic rat model of Alzheimer’s disease - Luodan Yang; Chongyun Wu; Yong Li; Yan Dong; Celeste Yin-Chieh Wu; Reggie Hui-Chao Lee; Darrell W. Brann; Hung Wen Lin; Quanguang Zhang (GeroScience, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

The roles of leaf area index and albedo in vegetation induced temperature changes across China using modelling and observations - Na Dong; Ming Luo; Zhen Liu; Junying Sun; Kailu Wu; Hui Lin (Climate Dynamics, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Effect of heat stress on oxidative damage and antioxidant defense system in white clover (Trifolium repens L.) - Hsiang-Lin Liu; Zhu-Xuan Lee; Tzu-Wei Chuang; Hui-Chen Wu (Planta, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Identification and phylogenetic analysis of five Crataegus species (Rosaceae) based on complete chloroplast genomes - Liwei Wu; Yingxian Cui; Qing Wang; Zhichao Xu; Yu Wang; Yulin Lin; Jingyuan Song; Hui Yao (Planta, 2021)

Alterinioella nitratireducens gen. nov., sp. nov., Isolated from Seawater in the West Pacific Ocean - Yan-Hui Kong; Cong Sun; Li-Li Guo; Lin Xu; Yue-Hong Wu; Xue-Wei Xu (Current Microbiology, 2021)

Ghrelin Affects Gastric Cancer Progression by Activating AMPK Signaling Pathway - Xiao-Lin Hu; Yong-Jun Zhu; Chang-Hua Hu; Li You; Juan Wu; Xiao-Yan He; Wen-Jie Huang; Zong-Hui Wu (Biochemical Genetics, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Rosanortriterpenes A–B, two new nortriterpenes from the fruits of Rosa laevigata var. leiocapus - Yu-Nong Tian; Bai-Lin Li; Juan-Juan Hu; Jin-Dan Xie; Wen-Jing Xiao; Ling-Hui Nie; Jie-Wei Wu (Natural Product Research, 2021)

Estimating Chinese residential populations from analysis of impervious surfaces derived from satellite images - Shan Wei; Yinyi Lin; Hongsheng Zhang; Luoma Wan; Hui Lin; Zhifeng Wu (International Journal of Remote Sensing, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Enhanced antioxidant capacity and upregulated transporter genes contribute to the UV-B-induced increase in blinin in Conyza blinii - Junyi Zhan; Qin Yang; Zhiyi Lin; Tianrun Zheng; Maojia Wang; Wenjun Sun; Tongliang Bu; Zizhong Tang; Chenglei Li; Xueyi Han; Haixia Zhao; Qi Wu; et al. (Environmental Science and Pollution Research, 2021)

Projections from Infralimbic Cortex to Paraventricular Thalamus Mediate Fear Extinction Retrieval - Yan Tao; Cheng-Yun Cai; Jia-Yun Xian; Xiao-Lin Kou; Yu-Hui Lin; Cheng Qin; Hai-Yin Wu; Lei Chang; Chun-Xia Luo; Dong-Ya Zhu (Neuroscience Bulletin, 2021)

Transcriptome and Metabolome Analyses of Sea Cucumbers Apostichopus japonicus in Southern China During the Summer Aestivation Period - Qiuhua Yang; Xusheng Zhang; Zhen Lu; Ruifang Huang; Ngoc Tuan Tran; Jianshao Wu; Fuyuan Yang; Hui Ge; Chenhui Zhong; Qian Sun; Chen Zhou; Qi Lin (Journal of Ocean University of China, 2021)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Nuclear Factor-κB Pathway Mediates the Molecular Pathogenesis of LMNA-Related Muscular Dystrophies - Yanbin Fan; Dandan Tan; Xu Zhang; Danyu Song; Xingzhi Chang; Shuang Wang; Hui Yan; Lin Ge; Haipo Yang; Carsten Bönnemann; Jingying Liu; Suxia Wang; et al. (Biochemical Genetics, 2020)

Mechanism of contractile dysfunction induced by serotonin in coronary artery in spontaneously hypertensive rats - Hao Wang; Xiao-Yan Gao; Fang Rao; Hui Yang; Zhao-Yu Wang; Lin Liu; Su-Juan Kuang; Qi Wu; Chun-Yu Deng; Jing-Song Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Two new species of Hortiboletus (Boletaceae, Boletales) from China - Hui-Jing Xie; Wen-Fei Lin; Shuai Jiang; Rou Xue; Lu-Ling Wu; Yu-Zhuo Zhang; Zhi-Qun Liang; Nian-Kai Zeng; Ming-Sheng Su (Mycological Progress, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Silencing of LRP1 Exacerbates Inflammatory Response Via TLR4/NF-κB/MAPKs Signaling Pathways in APP/PS1 Transgenic Mice - Yingying He; John Bosco Ruganzu; Quzhao Zheng; Xiangyuan Wu; Hui Jin; Xiaoqian Peng; Bo Ding; Chengheng Lin; Shengfeng Ji; Yanbing Ma; Weina Yang (Molecular Neurobiology, 2020)

The dominant model analysis of Sirt3 genetic variants is associated with susceptibility to tuberculosis in a Chinese Han population - Tao Wu; Lin Jiao; Hao Bai; Xuejiao Hu; Minjin Wang; Zhenzhen Zhao; Hui Xue; Binwu Ying (Molecular Genetics and Genomics, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Two new diprenylated flavanones from Derris laxiflora Benth - Hui-Chi Huang; Shih-Chang Chien; Ching-Chuan Kuo; Ming-Der Wu; Ming-Jen Cheng; Jih-Jung Chen; Hsi-Lin Chiu; Yueh-Hsiung Kuo (Natural Product Research, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Dynamic response and mechanical deformation properties of the soil cutting slope under train cyclic loads - Qiang Xie; Zhi-hui Wu; Chun-bo He; Jie Dong; Zhi-lin Cao; Li Liang (Arabian Journal of Geosciences, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Protein Arginine Methyltransferases in Cardiovascular and Neuronal Function - Alexandre Couto e Silva; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Garrett A. Clemons; HarLee E. Possoit; Mychal S. Grames; Chih-Feng Lien; Alireza Minagar; Reggie Hui-Chao Lee; Adam Frankel; Hung Wen Lin (Molecular Neurobiology, 2020)

Potential Genes Related to Levofloxacin Resistance in Mycobacterium tuberculosis Based on Transcriptome and Methylome Overlap Analysis - Hai-cheng Li; Hui-xin Guo; Tao Chen; Wei Wang; Zhu-hua Wu; Liang Chen; Hui-zhong Wu; Gao-po Xu; Xun-xun Chen; Lin Zhou (Journal of Molecular Evolution, 2020)
Drug-resistant Mycobacterium tuberculosis ( M. tuberculosis ) has become an increasingly serious public health problem and has complicated tuberculosis (TB) treatment. Levofloxacin (LOF) is an ideal anti-tuberculosis drug in clinical applications. However, the detailed molecular mechanisms of LOF-resistant M. tuberculosis in TB treatment have not been revealed. Our study performed transcriptome and methylome sequencing to investigate the potential biological characteristics of LOF resistance in M. tuberculosis H37Rv. In the transcriptome analysis, 953 differentially expressed genes (DEGs) were identified; 514 and 439 DEGs were significantly downregulated and upregulated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 97 pathways were enriched in this study. In the methylome analysis, 239 differentially methylated genes (DMGs) were identified; 150 and 89 DMGs were hypomethylated and hypermethylated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 74 pathways were enriched in this study. The overlap study suggested that 25 genes were obtained. It was notable that nine genes expressed downregulated mRNA and upregulated methylated levels, including pgi , fadE4 , php , cyp132 , pckA , rpmB1 , pfkB , acg , and ctpF , especially cyp132 , pckA , and pfkB , which were vital in LOF-resistant M. tuberculosis H37Rv. The overlapping genes between transcriptome and methylome could be essential for studying the molecular mechanisms of LOF-resistant M. tuberculosis H37Rv. These results may provide informative evidence for TB treatment with LOF.

Effects of reciprocal hybridization on cadmium accumulation in F1 hybrids of two Solanum photeinocarpum ecotypes - Lijin Lin; Caifang Wu; Jin Wang; Ming’an Liao; Daiyu Yang; Honghong Deng; Xiulan Lv; Hui Xia; Dong Liang; Qunxian Deng (Environmental Science and Pollution Research, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Water quality prediction based on recurrent neural network and improved evidence theory: a case study of Qiantang River, China - Lei Li; Peng Jiang; Huan Xu; Guang Lin; Dong Guo; Hui Wu (Environmental Science and Pollution Research, 2019)

Mercury–Organic Matter Interactions in Soils and Sediments: Angel or Devil? - Mei He; Lei Tian; Hans Fredrik Veiteberg Braaten; Qingru Wu; Jie Luo; Li-Mei Cai; Jiang-Hui Meng; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2019)

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Far-infrared Radiation Improves Motor Dysfunction and Neuropathology in Spinocerebellar Ataxia Type 3 Mice - Shin-Wu Liu; Jui-Chih Chang; Sheng-Fei Chuang; Ko-Hung Liu; Wen-Ling Cheng; Hui-Ju Chang; Huei-Shin Chang; Ta-Tsung Lin; Ching-Liang Hsieh; Wei-Yong Lin; Mingli Hsieh; Shou-Jen Kuo; et al. (The Cerebellum, 2019)

A thiopyran derivative with low murine toxicity with therapeutic potential on lung cancer acting through a NF-κB mediated apoptosis-to-pyroptosis switch - Liping Chen; Bixia Weng; Huimin Li; Haonan Wang; Qian Li; Xiaoyan Wei; Hui Deng; Sicen Wang; Chengxi Jiang; Renyu Lin; Jianzhang Wu (Apoptosis, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Clinical and microbiological characteristics of peritoneal dialysis-related peritonitis caused by Escherichia coli in southern Taiwan - Wei-Hung Lin; Chin-Chung Tseng; An-Bang Wu; Yu-Tzu Chang; Te-Hui Kuo; Jo-Yen Chao; Ming-Cheng Wang; Jiunn-Jong Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

An improved torque type gravity gradiometer with dynamic modulation - Jie Luo; Jia-Hao Xu; Qi Liu; Cheng-Gang Shao; Lin Zhu; Hui-Hui Zhao; Wei-Huang Wu (Acta Geodaetica et Geophysica, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Tobacco alpha-expansin EXPA4 plays a role in Nicotiana benthamiana defence against Tobacco mosaic virus - Li-Juan Chen; Wen-Shan Zou; Guo Wu; Hong-Hui Lin; De-Hui Xi (Planta, 2018)

A new ent -kaurane diterpene derivative from the stems of Eurya chinensis R.Br - Jia-Ling Song; Yao Yuan; Ling-Hui Nie; Bai-Lin Li; Xu-Bing Qin; Yan Li; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2018)

A quantitative method for risk assessment of agriculture due to climate change - Zhiqiang Dong; Zhihua Pan; Pingli An; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dong Wu; Jialin Wang; Dongliang Fan; et al. (Theoretical and Applied Climatology, 2018)

Effects of prenatal caffeine exposure on glucose homeostasis of adult offspring rats - Hao Kou; Gui-hua Wang; Lin-guo Pei; Li Zhang; Chai Shi; Yu Guo; Dong-fang Wu; Hui Wang (The Science of Nature, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Yangonindimers A-C, three new kavalactone dimers from Piper methysticum (kava) - Jia-Ling Song; Bai-Lin Li; Yao Yuan; Ling-Hui Nie; Jia Niu; David Chiu; Zhi-Fang Xu; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Two new geranylphenylacetate glycosides from the barks of Cinnamomum cassia - Jun-Fen Zeng; Hu-Cheng Zhu; Jian-Wu Lu; Lin-Zhen Hu; Jin-Chun Song; Yong-Hui Zhang (Natural Product Research, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Retraction Note to: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly(ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Therapeutic Hypothermia Enhances Cold-Inducible RNA-Binding Protein Expression and Inhibits Mitochondrial Apoptosis in a Rat Model of Cardiac Arrest - Lin Wu; He-liang Sun; Yu Gao; Kang-li Hui; Miao-miao Xu; Hao Zhong; Man-lin Duan (Molecular Neurobiology, 2017)

Ethaselen: a novel organoselenium anticancer agent targeting thioredoxin reductase 1 reverses cisplatin resistance in drug-resistant K562 cells by inducing apoptosis - Suo-fu Ye; Yong Yang; Lin Wu; Wei-wei Ma; Hui-Hui Zeng (Journal of Zhejiang University-SCIENCE B, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

RETRACTED ARTICLE: Advanced oxidation protein products induce chondrocyte death through a redox-dependent, poly (ADP-ribose) polymerase-1-mediated pathway - Wenbin Ye; Zhaoming Zhong; Siyuan Zhu; Shuai Zheng; Jun Xiao; Shaolian Song; Hui Yu; Qian Wu; Zhen Lin; Jianting Chen (Apoptosis, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Interleukin-35 (IL-35) inhibits proliferation and promotes apoptosis of fibroblast-like synoviocytes isolated from mice with collagen-induced arthritis - Yunxia Li; Suqin Wu; Yuxuan Li; Shenyi Jiang; Tiantian Lin; Liping Xia; Hui Shen; Jing Lu (Molecular Biology Reports, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Lack of association between polymorphisms in interleukin (IL)-12, IL-12R, IL-23, IL-23R genes and Takayasu arteritis in a Chinese population - Kun-Qi Yang; Yan-Kun Yang; Xu Meng; Ying Zhang; Xiong-Jing Jiang; Hai-Ying Wu; Hui-Min Zhang; Lei Song; Jin Bian; Dan Wen; Lin-Ping Wang; Xian-Liang Zhou (Inflammation Research, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Degradation of artificial sweetener saccharin in aqueous medium by electrochemically generated hydroxyl radicals - Heng Lin; Jie Wu; Nihal Oturan; Hui Zhang; Mehmet A. Oturan (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Vertical motions of tide gauge stations near the Bohai Sea and Yellow Sea - ShouHua Liu; ChangLin Chen; KeXiu Liu; Lin Mu; Hui Wang; XinRong Wu; JianLi Zhang; XiaoFeng Duan; Jia Gao (Science China Earth Sciences, 2015)

Hygromycin B-induced cell death is partly mediated by reactive oxygen species in rice (Oryza sativa L.) - Hui-Min Oung; Ke-Chun Lin; Tsung-Meng Wu; Nulu Naga Prafulla Chandrika; Chwan-Yang Hong (Plant Molecular Biology, 2015)

Defining the structural characteristics of annexin V binding to a mimetic apoptotic membrane - Jingxiong Lu; Anton P. Le Brun; Seong Hoong Chow; Takuya Shiota; Bo Wang; Tsung-Wu Lin; Guei-Sheung Liu; Hsin-Hui Shen (European Biophysics Journal, 2015)

Dysfunction Screening in Experimental Arteriovenous Grafts for Hemodialysis Using Fractional-Order Extractor and Color Relation Analysis - Ming-Jui Wu; Wei-Ling Chen; Chung-Dann Kan; Fan-Ming Yu; Su-Chin Wang; Hsiu-Hui Lin; Chia-Hung Lin (Cardiovascular Engineering and Technology, 2015)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Permeability Imaging as a Biomarker of Leptomeningeal Collateral Flow in Patients with Intracranial Arterial Stenosis - Hui Chen; Bing Wu; Guangming Zhu; Max Wintermark; Xinhuai Wu; Zihua Su; Xiao Xu; Chenglin Tian; Lin Ma; Weiwei Zhang; Xin Lou (Cell Biochemistry and Biophysics, 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

Temperature‐sensitive fitness cost of insecticide resistance in C hinese populations of the diamondback moth P lutella xylostella - Lin Jie Zhang; Yu Pu Jing; Xiao Hui Li; Chang Wei Li; Denis Bourguet; Gang Wu (Molecular Ecology, 2015)
Alleles conferring a higher adaptive value in one environment may have a detrimental impact on fitness in another environment. Alleles conferring resistance to pesticides and drugs provide textbook examples of this trade‐off as, in addition to conferring resistance to these molecules, they frequently decrease fitness in pesticide/drug‐free environments. We show here that resistance to chlorpyrifos, an organophosphate ( OP ), in Chinese populations of the diamondback moth, Plutella xylostella , is conferred by two mutations of ace1 – the gene encoding the acetylcholinesterase enzyme targeted by OP s – affecting the amino acid sequence of the corresponding protein. These mutations were always linked, consistent with the segregation of a single resistance allele, ace1R , carrying both mutations, in the populations studied. We monitored the frequency of ace1R (by genotyping more than 20 000 adults) and the level of resistance (through bioassays on more than 50 000 individuals) over several generations. We found that the ace1R resistance allele was costly in the absence of insecticide and that this cost was likely recessive. This fitness costs involved a decrease in fecundity: females from resistant strains laid 20% fewer eggs, on average, than females from susceptible strains. Finally, we found that the fitness costs associated with the ace1R allele were greater at high temperatures. At least two life history traits were involved: longevity and fecundity. The relative longevity of resistant individuals was affected only at high temperatures and the relative fecundity of resistant females – which was already affected at temperatures optimal for development – decreased further at high temperatures. The implications of these findings for resistance management are discussed.

Isolation and characterization of 25 polymorphic microsatellite loci from the Hynobius maoershanensis (Caudata: Hynobiidae) - Bing-jie Lin; Hua-yuan Huang; Zhong-hui Wei; Ze-ning Chen; Shao-neng Wang; Zheng-jun Wu (Conservation Genetics Resources, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Wheat straw and its biochar had contrasting effects on soil C and N cycling two growing seasons after addition to a Black Chernozemic soil planted to barley - Ya-Lin Hu; Feng-Ping Wu; De-Hui Zeng; Scott X. Chang (Biology and Fertility of Soils, 2014)

Estrogen improves the proliferation and differentiation of hBMSCs derived from postmenopausal osteoporosis through notch signaling pathway - Jin-Zhu Fan; Liu Yang; Guo-Lin Meng; Yan-shui Lin; Bo-Yuan Wei; Jing Fan; Hui-Min Hu; Yan-Wu Liu; Shi Chen; Jin-Kang Zhang; Qi-Zhen He; Zhuo-Jing Luo; et al. (Molecular and Cellular Biochemistry, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Mapping Soil Particle Size Fractions Using Compositional Kriging, Cokriging and Additive Log-ratio Cokriging in Two Case Studies - Xiao-Lin Sun; Yun-Jin Wu; Hui-Li Wang; Yu-Guo Zhao; Gan-Lin Zhang (Mathematical Geosciences, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Microsatellite primer development for the king ratsnakes Elaphe carinata (Colubridae) - Yan-Qing Wu; Rong-Fang Wang; Long-Hui Lin; Yan-Fu Qu (Conservation Genetics Resources, 2014)

A loess landslide induced by excavation and rainfall - Jun-Jie Wang; Yue Liang; Hui-Ping Zhang; Yang Wu; Xin Lin (Landslides, 2014)

Isolation, Identification and Characterization of Lactic Acid Bacteria From Shao-jiou-luo (Fermented Zoned Cerith), a Traditional Fermented Food in Taiwan - Yi-Sheng Chen; Hui-Chung Wu; Huei-Yin Lo; Wen-Hsuan Hsu; Wan-Chen Lin; Bo-Ya Lin (Journal of Aquatic Food Product Technology, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Rural livelihoods and climate variability in Ningxia, Northwest China - Yue Li; D. Conway; Yanjuan Wu; Qingzhu Gao; S. Rothausen; Wei Xiong; Hui Ju; Erda Lin (Climatic Change, 2013)

Quantitative analysis of the association between interleukin-10 1082A/G polymorphism and susceptibility to sepsis - Lin Ouyang; You-Di Lv; Can Hou; Guo-Bao Wu; Zhi-Hui He (Molecular Biology Reports, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

Effects of temperature on copper resistance in daf-21 mutant and Hsp90 expression of Caenorhabditis elegans - Yun-Biao Wang; Jia-Lin Gao; Dong-Hui Wu (Paddy and Water Environment, 2013)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

Rice heading date retrieval based on multi-temporal MODIS data and polynomial fitting - Hongshuo Wang; Jinsong Chen; Zhifeng Wu; Hui Lin (International Journal of Remote Sensing, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Analysis of the expression of BohLOL1, which encodes an LSD1-like zinc finger protein in Bambusa oldhamii - Sheng-Hsiung Yeh; Choun-Sea Lin; Fu-Hui Wu; Ai-Yu Wang (Planta, 2011)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Zebrafish HSC70 promoter to express carp muscle-specific creatine kinase for acclimation under cold condition - Chih-Lu Wu; Ta-Hui Lin; Tien-Lin Chang; Hsi-Wen Sun; Cho-Fat Hui; Jen-Leih Wu (Transgenic Research, 2011)

New epothilone congeners from Sorangium cellulosum strain So0157-2 - Ji-Dong Wang; Nan Jiang; Hui Zhang; Lin-Ping Ying; Chuan-Xi Wang; Wen-Sheng Xiang; Bo Wu; Hai-Bin Wang; Hua Bai (Natural Product Research, 2011)

Tetraethylammonium enhances the rectal and colonic motility in rats and human in vitro - Zhe Li; Zhi-Lin Xu; Jing Liang; Ji-Chao Wu; Chao-Wei Hu; Hui Xie; Wen-Chao Ma; Hong-Chi Jiang; Bao-Feng Yang; De-Li Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Highly enantioselective bioreduction of N-methyl-3-oxo-3-(thiophen-2-yl) propanamide for the production of (S)-duloxetine - Chuan-Gen Tang; Hui Lin; Chao Zhang; Zhang-Qin Liu; Tao Yang; Zhong-Liu Wu (Biotechnology Letters, 2011)

Sensitivity Analysis of Phenol Degradation with Sulfate Reduction Under Anaerobic Conditions - Yen-Hui Lin; Chih-Lung Wu (Environmental Modeling & Assessment, 2011)

Electrospun PLGA–silk fibroin–collagen nanofibrous scaffolds for nerve tissue engineering - Guanglin Wang; Xudong Hu; Wei Lin; Changchao Dong; Hui Wu (In Vitro Cellular & Developmental Biology - Animal, 2011)

Rational design of styrene monooxygenase mutants with altered substrate preference - Abeer Ahmed Qaed; Hui Lin; De-Fang Tang; Zhong-Liu Wu (Biotechnology Letters, 2011)

Genetic characterization of ticks from southwestern Romania by sequences of mitochondrial cox1 and nad5 genes - Lidia Chitimia; Rui-Qing Lin; Iustin Cosoroaba; Xiang-Yun Wu; Hui-Qun Song; Zi-Guo Yuan; Xing-Quan Zhu (Experimental and Applied Acarology, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

A Meteorological Potential Forecast Model for Acid Rain in Fujian Province, China - Yi Yong Cai; Chang Cheng Lin; Jing Xiong Liu; De Hui Wu; Dong Ying Lian; Bin Bin Chen (Bulletin of Environmental Contamination and Toxicology, 2010)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Naringenin-Loaded Nanoparticles Improve the Physicochemical Properties and the Hepatoprotective Effects of Naringenin in Orally-Administered Rats with CCl4-Induced Acute Liver Failure - Feng-Lin Yen; Tzu-Hui Wu; Liang-Tzung Lin; Thau-Ming Cham; Chun-Ching Lin (Pharmaceutical Research, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Effects of Ethanol on Benzene Degradation Under Denitrifying Conditions - Yaoguo Wu; Yunfeng Li; Lin Hui; Ying Tan; Song Jin (Bulletin of Environmental Contamination and Toxicology, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Establishment of a cDNA library from Bambusa edulis Murno in vitro-grown shoots - Nein-Tzu Liu; Fu-Hui Wu; Hsin-Sheng Tsay; Wei-Chin Chang; Choun-Sea Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Study of growth and body composition of red snapper Lutjanus erythropterus fed diets containing Escherichia coli expressing recombinant tilapia insulin-like growth factor-I - Wen-Liang LIAO; Hsin-Hui LU; Shun-Kuo HUANG; Jen-Leh WU; Jan-Hsiung HUANG; En-Chung LIN (Fisheries Science, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Strategies and mechanisms of plant virus resistance - Shih-Shun Lin; Rossana Henriques; Hui-Wen Wu; Qi-Wen Niu; Shyi-Dong Yeh; Nam-Hai Chua (Plant Biotechnology Reports, 2007)

Chloroplast genome aberration in micropropagation-derived albino Bambusa edulis mutants, ab1 and ab2 - Nien-Tsu Liu; Wann-Neng Jane; Hsin-Sheng Tsay; Hui Wu; Wei-Chin Chang; Choun-Sea Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Analysis of mesoscale convective systems over Tibetan Plateau in summer - Zhong-yang Guo; Xiao-yan Dai; Jian-ping Wu; Hui Lin (Chinese Geographical Science, 2006)

Immunohistochemical Detection of Apoptotic Proteins, p53/Bax and JNK/FasL Cascade, in the Lung of Rats Exposed to Cigarette Smoke - Cheng-Hsun Wu; Hui-Hsuan Lin; Fu-Pin Yan; Cheng-Hua Wu; Chau-Jong Wang (Archives of Toxicology, 2006)

Investigation of iodine concentration in salt, water and soil along the coast of Zhejiang, China - Ying-li Lu; Ning-jian Wang; Lan Zhu; Guo-xing Wang; Hui Wu; Lin Kuang; Wen-ming Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Image analysis of geostationary meteorological satellite for monitoring movement of mesoscale convective systems over Tibetan plateau - Zhong-yang Guo; Xiao-yan Dai; Wu Jian-ping; Lin Hui (Chinese Geographical Science, 2005)

Antitermitic and Antifungal Activities of Essential Oil of Calocedrus formosana Leaf and Its Composition - Sen-Sung Cheng; Chi-Lin Wu; Hui-Ting Chang; Yu-Ting Kao; Shang-Tzen Chang (Journal of Chemical Ecology, 2004)

A Method for Locating Influential Pollution Sources and Estimating Their Contributions - Ching-Ho Lin; Yee-Lin Wu; Ken-Hui Chang; Chin-Hsing Lai (Environmental Modeling & Assessment, 2004)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Role of tumor metastasis suppressor gene KAI1 in digestive tract carcinomas and cancer cells - Qiao Wu; Yuan Ji; Ming-qing Zhang; Yu-qiang Chen; Fu Chen; Da-lin Shi; Zong-hui Zheng; Yao-jian Huang; Wen-jin Su (Cell and Tissue Research, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)